2011
DOI: 10.1073/pnas.1015024108
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying structure and performance diversity for sets of small molecules comprising small-molecule screening collections

Abstract: Using a diverse collection of small molecules we recently found that compound sets from different sources (commercial; academic; natural) have different protein-binding behaviors, and these behaviors correlate with trends in stereochemical complexity for these compound sets. These results lend insight into structural features that synthetic chemists might target when synthesizing screening collections for biological discovery. We report extensive characterization of structural properties and diversity of biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 72 publications
3
63
0
Order By: Relevance
“…These compounds are compared to the Maybridge Screening Collection (http://www.maybridge.com/portal/alias__Rainbow/lang__en/tabID__146/DesktopDefault.aspx), the collection of the Molecular Library Program (MLP) of the National Institutes of Health (NIH) [11], and compounds curated in the Page 3 of 11 A c c e p t e d M a n u s c r i p t ChEMBL database [12]. The Maybridge collection was chosen as a representative screening library from commercial sources because of its diversity-based character and previous use in screening collections comparisons [13]. The MLP library was selected because of the similar collaborative nature of the MLP and ELF programs, and the ChEMBL database because of the medicinal chemistry relevance of the compounds curated therein.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are compared to the Maybridge Screening Collection (http://www.maybridge.com/portal/alias__Rainbow/lang__en/tabID__146/DesktopDefault.aspx), the collection of the Molecular Library Program (MLP) of the National Institutes of Health (NIH) [11], and compounds curated in the Page 3 of 11 A c c e p t e d M a n u s c r i p t ChEMBL database [12]. The Maybridge collection was chosen as a representative screening library from commercial sources because of its diversity-based character and previous use in screening collections comparisons [13]. The MLP library was selected because of the similar collaborative nature of the MLP and ELF programs, and the ChEMBL database because of the medicinal chemistry relevance of the compounds curated therein.…”
Section: Introductionmentioning
confidence: 99%
“…To generate the CSR curves, the scaffolds are ordered by their frequency of occurrence (most to least common). Then, the fraction of scaffolds is plotted on the x-axis and the fraction of compounds that contain those scaffolds on the The structures were retrieved from Clemons et al [19].…”
Section: Scaffold Diversitymentioning
confidence: 99%
“…Several chemoinformatic analyses of natural products databases have been published. Examples of recent analysis include a comparison of the molecular complexities and structural diversities of three databases, including a natural product collection, and how these properties were related to specificity and diversity of biological performance (19). The authors demonstrated that compound specificity was associated with molecular complexity.…”
mentioning
confidence: 99%
“…This approach aimed at guiding the creation of effective screening collections for cell-based, phenotypic HTS. We also applied parallel biochemical assay profiling (15) to explore relationships between protein-binding performance diversity and similar chemical features as well as the role of origins of compounds. The latter study addresses the problem of defining effective screening collections for biochemistry-based HTS involving protein binding and activity modulation (for example, enzyme inhibition).…”
mentioning
confidence: 99%